2021
DOI: 10.5344/ajev.2021.20058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three Commercial Over-the-Row Sprayer Technologies in Eastern Washington Vineyards

Abstract: Washington wine grape growers are rapidly adopting vineyard management technologies such as mechanical pruners and harvesters but have been slower to adopt new chemical application technologies. Therefore, this study was aimed at generating technical information about commercial over-the-row sprayers deposition and drift, which could be used by growers during sprayer selection and optimization for different vineyard systems and wine grape canopies. Three commercial sprayer technologies, i.e. multi-fan heads, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Such coverage trends can be explained based on the spatial characteristic of the citrus canopy under various cultivation patterns. The citrus canopy under P1 was mostly an open-centered type with high canopy density in the middle layers (Figure 5a), which easily formed interlaminar closures in the canopy [31], resulting in reduced droplets penetration and spray coverage in the bottom layers [32,33]. On the contrary, citrus under P2 and P3 would have narrower canopy width and sparser foliage, which facilitated better spray deposition in the middle layers and bottom layers.…”
Section: Spray Coverage For Aaes Under Different Cultivation Patternsmentioning
confidence: 99%
“…Such coverage trends can be explained based on the spatial characteristic of the citrus canopy under various cultivation patterns. The citrus canopy under P1 was mostly an open-centered type with high canopy density in the middle layers (Figure 5a), which easily formed interlaminar closures in the canopy [31], resulting in reduced droplets penetration and spray coverage in the bottom layers [32,33]. On the contrary, citrus under P2 and P3 would have narrower canopy width and sparser foliage, which facilitated better spray deposition in the middle layers and bottom layers.…”
Section: Spray Coverage For Aaes Under Different Cultivation Patternsmentioning
confidence: 99%
“…The spray deposition and drift collection and processing methods described below were similar to those done by McCoy et al 26 with a few modifications as indicated below. As with that previous study, a fluorescent tracer (Keystone TM Pyranine 10G; Milliken TM ; Spartanburg, SC, USA) was used as a tracer dye for collecting spray droplet canopy deposition, captured aerial drift, and ground deposition on 5 × 5 cm plastic cards.…”
Section: Spray Deposition and Drift Collection And Processingmentioning
confidence: 99%
“…Captured aerial drift and ground deposition data was increased between 2018 and 2019 to ensure enough sample size based upon previous data collection with other field trials. 26 The captured aerial drift and ground deposition were collected from the center vine of each repetition in 2018 (n=3) and the center three vines of each repetition in 2019 and 2020 (n=9). Deposition and drift collection procedures.…”
Section: Spray Deposition and Drift Collection And Processingmentioning
confidence: 99%
“…Nozzle failure is often caused by wear. The abrasive effects of sand, kaolin, and other impurities in the water, as well as abrasive pesticides (such as insecticides made from natural materials like pumice, corundum, or diatomite), is the cause of wear on the working solution [14][15][16]. The change in nozzle tip shape and the effect on spray angle is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%